Knowledge Creation and Knowledge Sharing as Determinants of Knowledge Utilization among Selected University Libraries in South-West Nigeria - Adewuyi Olugbenga Wale (COVENANT JOURNAL OF LIBRARY AND INFORMATION SCIENCE, 2021)
Purpose: The paper examined the relationship between knowledge creation, knowledge sharing and knowledge utilization in selected university libraries in the South-West, Nigeria. Design/methodology/approach: Descriptive survey research design was used for the study, using a self-developed and pretested and validated questionnaire as research instrument. The pre-tested was done at the Olabisi Onabanjo University, AgoIwoye, Ogun State, which was different from the selected Universities. 185 copies of the questionnaire were administered on the respondents, using total enumeration technique. Descriptive statistics such as frequency, percentages, mean and standard deviation were used to analyze the research questions, while inferential statistics such as multiple regression analysis were used to test the hypotheses. Findings: The study discovered that there is a significant relationship between knowledge creation and knowledge utilization in Nigerian University Libraries in South-West, Nigeria. The study also established a positive significant relationship between knowledge sharing and knowledge utilization in selected university libraries in South-West, Nigeria (r = .316, p <.05). However, even though the study discovered that there were positive influences of both knowledge creation and knowledge sharing on knowledge utilization in the studied university libraries in South-West, Nigeria but knowledge creation has the highest effect on knowledge utilization than the knowledge sharing. Originality/Value: Several studied have been conducted on knowledge sharing either on its own or in relationship with other variables especially in library literature but it seem none have been done to examine the relationship between the three interwoven constructs of knowledge management vis-a-vis knowledge creation, knowledge sharing and knowledge utilization. Thus makes this study unique. The result may be useful by University Management to further strengthen knowledge management practices.